PENGARUH DIGITAL MARKETING TERHADAP PENJUALAN INDIHOME (STUDI PADA PT. TELEKOMUNIKASI INDONESIA DI DAERAH BSD TANGERANG SELATAN) - Gina Emily Napitupulu; Remista Simbolon (Jurnal Ekonomis, 2022)
This study aims to describe and analyze the influence of digital marketing on Indihome sales in the BSD South Tangerang area. This study uses a questionnaire via google form as a research instrument. Data processing using SPSS v25 software uses the correlation coefficient test, t test, coefficient of determination, and simple linear regression. The correlation coefficient test r count is 0.366, which means that sales have a not strong relationship with digital marketing. The t-test results show that digital marketing has a significant effect on sales as evidenced by the t-count value of 3.453 > t-table 1.990 and the digital marketing variable is indicated by a determination test of 13.4%, which means it has a negative effect on sales while the rest is influenced by other factors outside of this research. Simple linear regression shows Y= = 26,376 + 0.244X as a formula, which means that if digital marketing has no sales then consumers are at 26,376 and if digital marketing increases by 1 unit then sales increase by 0.244 units. It can be seen that digital marketing has a significant effect on sales.